Identity and emotion of university English teachers during curriculum reform in China. Issue 4 (2nd October 2022) - Yip, Jesse W. C.; Huang, Jing; Teng, Mark Feng
Abstract: Limited attention has been given to the emotions of university English teachers in their identity constructions in the context of curriculum reform in China. Drawing upon the identity control theory (ICT), this qualitative study examines how six teachers negotiate their emotions during curriculum reform in China. Data were collected through in-depth interviews. Findings indicate that teachers experience a variety of emotions in response to the curriculum reform and that the emotions are triggered by teachers' identity constructions. Based on the findings and ICT, this study proposes a model that delineates the interplay between self-identity, performance outcome, and teacher emotion in the context of curriculum reform. The model explicates that congruence between teachers' self-identities and the identities imposed by the reform contributes to positive emotions and vice versa. Adding to the original ICT, this study suggests that teachers' performance outcomes (i.e. teaching outcome and student performance) are likely to influence the (non-)verification of role performance and teacher emotion. In addition, this study reveals the factors that influence teachers' role performances in the reform, including rapid changes in education policy, stressful teaching evaluations, the instruction of ideological and political thoughts in English courses, and teachers' insufficient computer skills.